Managing the economic development of the country on the principles of ESG and digitalisation - M. S. Mokiy (Вестник университета, 2022)
The article substantiates the thesis that the implementation of the principles of ESG (environment, society and corporate governance) at the level of the country’s economy requires a revision of the ontological provisions of economics. The application of the system-transdisciplinary concept allows us to interpret economic relations as a fragment of humanity’s relations with nature. Economic relations arose as a systemic necessity for the existence and development of mankind. It is shown that in the system of “economic relations” a set of values determines the nomenclature and assortment of goods, methods of production, exchange and distribution. From the point of view of system ontology, the basic element of the system of economic relations is the “household”. Therefore, the objective function of managing the development of economic relations at the country level should be to improve the welfare of each household. The identified immanent attributes of the “economic relations” system and the designation of their systemic role allowed us to conclude that the main task of management is to change the value system that meets the requirements of the coevolutionality of the system development. It is shown that such an ontological interpretation is most consistent with the principles of ESG and the requirements of sustainable development of the human community. On this basis, the ranking of management tasks was made and the directions of digitalisation of management processes at the country level were identified.